(untitled) (The Pakistan Development Review, 2014)
Energy is the basic ingredient for economic growth and development [Lorde, et al. (2010)]. Presently demand for energy has significantly increased due to the overall expansion of economic and industrial activity in all important economic sectors e.g. industry, agriculture, and services. In addition to the expansion of economic activity and subsequent increase in energy demand at industrial level, population growth and increased consumption are also adding to the demand for energy [OECD (2011)]. In other words, modern economy has become highly dependent on energy resources. In order to meet the increased energy demand and ensure its sustainable supply, there is a need to have strong and robust plans with all options to consider at various levels.